USHUL AL-NAHWI: Kajian tentang Dasar Bangunan Sintaksis Arab - Ra'uf, Abdullah Zainur (ULUL ALBAB Jurnal Studi Islam, 2004)
Muhammad Ahmad Qasim argued that ushul al-nahwi is a study about nahwu propositions (Arabic syntax) in general from either its reasoning and method It is mainly regarded as reference as many linguists meet linguistics problems abqut nahwu. Each language, generally known, has structure and pattern so systematic that it can clearly understandable and acceptable to people. Moreover, the differences within ushul al-nahwi many linguistics meet can basically be referred to two main ways; alsima' and al-naqli.